Enzymatic biosynthesis and biological evaluation of novel 17-AAG glucoside as potential anti-cancer agents. Issue 15 (1st August 2020) - Li, Hong-Mei; Li, Bohan; Sun, Xiaolong; Ma, Hui; Zhu, Meilin; Dai, Yiquan; Ma, Tao; Li, Yu; Hong, Young-Soo; Wu, Cheng-Zhu
Graphical abstract: Highlights: A novel 17-AAG glucoside (1 ) have been synthesized by the in vitro enzymatic glycosylation. Compound 1 displayed better water-solubility than 17-AAG. Compound 1 exhibited greater potential in vivo anti-tumor efficacy than 17-AAG. Abstract: A novel 17-allylamino-17-demethoxygeldanamycin (17-AAG) glucoside (1 ) was obtained from in vitro enzymatic glycosylation using a UDP-glycosyltransferase (YjiC). The water-solubility of compound 1 was approximately 10.5 times higher than that of the substrate, 17-AAG. Compound 1 showed potential anti-proliferative activities against five human cancer cell lines, with IC50 values ranging from 5.26 to 28.52 μM. Further studies also indicated that compound 1 could inhibit the growth of CNE-2Z cells by inducing the degradation of Hsp90 client proteins (Akt, c-Raf, Bcl-2, and HIF-1α). In addition, compound 1 showed greater potential anti-tumor efficacy than 17-AAG in nude mice xenografted with CNE-2Z cells. Therefore, we suggest that in vitro enzymatic glycosylation is a powerful approach for the structural optimization of 17-AAG.